Learn SolidWorks 2022 - Almattar, Tayseer (Packt Publishing, 2022)
Get to grips with leading 3D engineering and product design application to design robust 3D models and achieve CSWA and CSWP certification Key Features Gain comprehensive insights into the core aspects of 3D modeling's mechanical parts Learn how to generate assembly designs with both standard and advanced mates Discover design practices for both 2D as well as 3D modeling and prepare to achieve CSWP and CSWA certification Book Description SOLIDWORKS is the leading choice for 3D engineering and product design applications across industries such as aviation, automobile, and consumer product design. This book helps you to get up and running with SOLIDWORKS and understand each new concept and tool with the help of easy-to-follow exercises. You'll begin with the basics, exploring the software interface and finding out how to work with drawing files. The book then guides you through topics such as sketching, building complex 3D models, generating dynamic and static assemblies, and generating 2D engineering drawings to prepare you to take on any design project. You'll also work with practical exercises to get hands-on experience with creating sketches, 3D part models, assemblies, and drawings. To reinforce your understanding of SOLIDWORKS, the book is supplemented by downloadable files that will help you to understand the concepts and exercises more easily. Finally, you'll also work on projects for 3D modeling objects inspired by everyday life. By the end of this SOLIDWORKS book, you'll have gained the skills you need to create professional 3D mechanical models using SOLIDWORKS and be able to prepare effectively for the Certified SOLIDWORKS Associate (CSWA) and Certified SOLIDWORKS Professional (CSWP) exams. What you will learn Understand the fundamentals of SOLIDWORKS and parametric modeling Create professional 2D sketches as bases for 3D models using simple and advanced modeling techniques Use SOLIDWORKS drawing tools to generate standard engineering drawings Evaluate mass properties and materials for designing parts and assemblies Join different parts together to form static and dynamic assemblies Discover expert tips and tricks to generate different part and assembly configurations for your mechanical designs Who this book is for This book is for aspiring engineers, designers, makers, draftsmen, and hobbyists looking to get started with SOLIDWORKS and explore the software. Individuals who are interested in becoming Certified SOLIDWORKS Associates (CSWAs) or Certified SOLIDWORKS Professionals (CSWPs) will also find this book useful. No specific background is needed to follow the concepts in the book as it starts from the basics of SOLIDWORKS. However, basic theoretical knowledge of 3D modeling will be helpful to get the most out of this book.